Hoxa9 Regulates Flt3 in Lymphohematopoietic Progenitors - Gwin, Kimberly (2010)
Early B cell factor (EBF) is a transcription factor essential for specification and commitment to the B cell fate. In this study, we show downregulation of a developmentally regulated cluster of hoxa genes, notably hoxa9, coincides with induction of EBF at the Pro-B cell stage of B cell differentiation. Analysis of the hematopoietic progenitor compartment in Hoxa9(−/−) mice revealed significantly reduced frequencies and expression levels of Flt3, a cytokine receptor important for lymphoid priming and the generation of B cell precursors (BCPs). We show that Hoxa9 directly regulates the flt3 gene. Chromatin immunoprecipitation analysis revealed binding of Hoxa9 to the flt3 promoter in a lymphoid progenitor cell line. Knockdown of Hoxa9 significantly reduced Flt3 transcription and expression. Conversely, forced expression of Hoxa9 increased Flt3 transcription and expression in a Pro-B cell line that expressed low levels of Flt3. Hoxa9 inversely correlated with ebf1 in ex vivo-isolated bone marrow progenitors and BCPs, suggesting that EBF might function to silence a Hoxa9 transcriptional program. Restoration of EBF function in an EBF(−/−) cell line induced B lineage gene expression but did not directly suppress hoxa9 transcription, revealing alternate mechanisms of Hoxa9 regulation in BCPs. These data provide new insight into Hoxa9 function and regulation during lymphoid and B cell development. Furthermore, they suggest that failure to upregulate Flt3 provides a molecular basis for the lymphoid/early B cell deficiencies in Hoxa9(−/−) mice.